URGENCY OF MARRIAGE AGE MATURITY: REVIEWING THE GOVERNMENT'S RESPONSE TO THE PHENOMENON OF UNDERAGE MARRIAGE - Mukhammad Taufan Perdana Putra; Weppy Susetiyo (Universitas Islam Balitar, 2020)
This article discusses how the development of efforts to marriage age maturity in Indonesia. This effort is not only as a manifestation of the government in responding to marital problems such as the prevalence of underage marriages, also as another means to curb the behavior of some people who still often deviate marital age regulations through requests for marriage dispensation in court. The research findings conclude that there are important arguments that need to be considered for the government's efforts to reduce the rate of underage marriage in Indonesia, such as through the marriage age maturity program. This can be started by building integration or cooperation between institutions in order to maximize the function of the rule of law and their respective social roles, so that underage marriage can be minimized as well as possible.